Vers une université digitalisée ? Ce que le distanciel fait au travail des enseignant·es-chercheur·es. - Déborah Cohen; Christophe Roiné; Paul Bouffartigue; Olivier Cléach; Guillaume Tiffon (La Nouvelle Revue du Travail, 2023)
Distance education and training have developed strongly with the Covid-19 crisis. Since the end of the crisis, face-to-face teaching has once again become the rule and distance learning the exception. Have the uses of distance learning in teaching and research really disappeared? In practice, are there no traces of it left in the way academics carry out their work? Based on the contributions of two colleagues, this controversy aims to question the practices and points of view of academics on the use of distance learning, both in terms of their conceptions of the profession, the meaning they give to it and the relationship they have with the transmission of knowledge, but also from the point of view of how each of them has experienced the health crisis situation.